Analysis of the Ricinodendron heudelotii × Theobroma cacao L. Interaction in Traditional Agroforestry Systems in Côte d’Ivoire - Jean-Claude N’Zi; Jean-Parfait Kouadio Brou; Alban Antoine Kacou M’Bo; Wenceslas Affessi; Henri Kouadio Kouassi; Christophe Kouame (Horticulturae, 2022)
The objective of this study was to improve cacao (Theobroma cacao) production through its association with a woody species, such as Ricinodendron heudelotii, in western Côte d’Ivoire. To do this, a design of two transects (10 m and 20 m) was installed around the species in 5 localities (Buyo, Duekoué, Guéyo, San-Pedro, and Soubré). The diameter at the breast height of the tree, the height, the number of fruits, the above biomass, and its carbon stock were measured. Results showed morphological variability of R. heudelotii according to the localities. The presence of the species within cacao trees reduces the rate of pod rot, stabilizes the rate of pods eaten away, and increases the biomass production and the carbon storage of cacao trees. The distance between the two species had no impact on the vigor and the yield of cacao trees. However, cacao density in the 10 m line was reduced compared to that of the 20 m. Therefore, the integration of R. heudelotii into cacao agroforestry systems could improve cacao production. That is why the reduction of cacao density, as well as the use of more suitable varieties of cacao, should be considered for the sustainability of this system.